MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI PEMANFAATAN MEDIA BAHAN BEKAS PADA ANAK USIA 5-6 TAHUN DI KELOMPOK B1 TK. ISTIQOMAH BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Hayati Hayati; Zulkifli N Zulkifli N; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : On the basis of this problem is the lack of increased fine motor skills of children, some children may not be able to cut out neatly, filling pattern still belumpenuh, coloring is not neat and so on. Therefore, it is necessary efforts to improve fine motor skills of children through the use of scrap materials media.The purpose of this study was to determine the fine motor skills of children at the age of 5-6 years in kindergarten Istiqomah Bagansiapiapi District of Bangko Rokan Hilir. This research is a classroom action research conducted in two cycles. Data collection tool used in this study is in the form of observation sheet. The sample in this study were 15 children sebnyak consisting of 8 boys and 7 girls. Based on an analysis of two cycles assessment process improvements, penigkatan that occur are from prasiklus to the first cycle of 44.17%, the first cycle to the second cycle of 33.33% and an increase of prasiklus to cycle II of 71.85%. From the results of these studies concluded that through the utilization of scrap materials media can improve fine motor skills of children in the 5-6 year old children in Nursery child Istiqomah Bagansiapiapi District of Bangko Rokan Hilir.Keywords: improve fine motor, scrap materials